1994
DOI: 10.1111/j.1651-2227.1994.tb13223.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of chronic inflammatory bowel disease

Christian P Braegger

Abstract: The aetiology and pathogenesis of chronic inflammatory bowel disease are unknown. However, there is circumstantial evidence that immune mechanisms may play a significant role in mediating the gut lesion and various systemic manifestations. The role of the cellular immune system, soluble mediators, including proinflammatory and immunoregulatory cytokines, humoral immunity and mucosal complement activation will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
0
32
0
3
Order By: Relevance
“…Discute-se também como se estabelece a reação inflamatória, como ela progride e se perpetua, sem se ter algum esclarecimento a respeito 4 .…”
Section: Etiopatogêneseunclassified
See 1 more Smart Citation
“…Discute-se também como se estabelece a reação inflamatória, como ela progride e se perpetua, sem se ter algum esclarecimento a respeito 4 .…”
Section: Etiopatogêneseunclassified
“…Os marcadores gené-ticos estudados mostram um aumento de freqüência de antígenos HLA-D27 entre os portadores de RCUI e espondilite anquilosante 6 , e no Japão o antígeno mais freqüente associado à RCUI é o HLA-B5-DR2, e 5) fator imunológico -a participação do sistema imunológico na etiopatogênese da RCUI é aceita pela maioria dos autores e, embora haja uma pleíade de trabalhos sobre o assunto, não está ainda definido o mecanismo básico envolvido. Elementos imunológicos humorais e celulares estão comprovadamente participando da reação inflamatória na mucosa, tais como, aumento de imunócitos formadores de IgG1 e IgG3, mastó-citos macrofágos e outros, mas ainda não ficou estabelecida a importância de cada um 4,7,9 .…”
Section: Etiopatogêneseunclassified
“…Clinically, IBD is subdivided into Crohn's disease and ulcerative colitis. Although the detailed etiology of IBD remains to be determined, there is circumstantial evidence to link IBD to the mucosal immune system's failure to attenuate immunity to luminal Ags (19,20).…”
mentioning
confidence: 99%
“…Pro-inflammatory monokines, such as IL-1, TNF, and IL-6, as well as T cell lyrnphokines, such as IL-2 and IFNy, have been observed in IBD tissues (122,123). Through the use of gene-targeted disruption in mice (knock out mice), it has recently been shown that the targeted disruption of IL-10, IL-2, and the T cell receptor results in mice that phenotypically have colon lesions very similar to the lesions of ulcerative colitis (124)(125)(126).…”
Section: The Jawstat Pathway and Chronic Inflammationmentioning
confidence: 99%